2017
DOI: 10.1038/s41598-017-07748-x
|View full text |Cite
|
Sign up to set email alerts
|

Bioactivity-Guided Fractionation of Pine Needle Reveals Catechin as an Anti-hypertension Agent via Inhibiting Angiotensin-Converting Enzyme

Abstract: Hypertension has been recognized as one of the highest risk factors for cardiovascular diseases. Anti-hypertension agent screening and development has been recognized as a pharmaceutical therapy approach for the cardiovascular diseases treatment. Many kinds of traditional Chinese medicines, such as pine needle, have been used for the treatment of hypertension for a long time, but the bioactive ingredients which responsible for their therapeutic effectiveness are remain unclear. Therefore, screening bioactive c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…These compounds have been reported to have antihypertensive properties (Silva et al, 2013) that improve cardiac hypertrophy and myocardial fibrosis (Zhao et al, 2017). Catechin was found to come from Moutan Cortex, which has antihypertensive properties that inhibit angiotensinconverting enzyme (He, 2017). In summary, previous studies have confirmed that the main active constituents of ZSHLF may play roles as antihypertensive, anti-myocardial fibrosis, and cardioprotective agents and may be part of the material basis for ZSHLF function.…”
Section: Discussionmentioning
confidence: 87%
“…These compounds have been reported to have antihypertensive properties (Silva et al, 2013) that improve cardiac hypertrophy and myocardial fibrosis (Zhao et al, 2017). Catechin was found to come from Moutan Cortex, which has antihypertensive properties that inhibit angiotensinconverting enzyme (He, 2017). In summary, previous studies have confirmed that the main active constituents of ZSHLF may play roles as antihypertensive, anti-myocardial fibrosis, and cardioprotective agents and may be part of the material basis for ZSHLF function.…”
Section: Discussionmentioning
confidence: 87%
“…Studies on the hypotensive activity of the purified flavonoids have been cited above (see M. alba). Here, two recent researches have to be mentioned which demonstrate the ACE inhibition activity of catechin (He, 2017) and the NO levels stimulation by epicatechin (Fig. 7) (Ramirez-Sanchez et al, 2018).…”
Section: Terpenesmentioning
confidence: 98%
“…Flavonoids are widely distributed in plants, fulfilling many functions. They may also act as chemical messengers and physiological regulators …”
Section: Flavonoidmentioning
confidence: 99%